Pharmacokinetic Interaction Between Bay Leaves (Syzygium polyanthum) Infusion and Captopril in Rats - Amran Nur; Septian Dwi Rahmat; Ermalyanti Fiskia; Marhamah Marhamah (Journal of Pharmascience, 2026)
Captopril, an ACE inhibitor, is commonly prescribed as first-line therapy for hypertension. In practice, patients often combine synthetic drugs with herbal remedies such as bay leaves (Syzygium polyanthum), raising concerns about potential interactions. This study investigated the effect of bay leaf infusion on the pharmacokinetic profile of Captopril in white rats (Rattus norvegicus). Ten rats were divided into two groups: group 1 received 25 mg of Captopril, while group 2 received the same dose in combination with bay leaf infusion. Blood samples were collected via the tail vein at 0; 0.5; 1; 2; 4; 6; 12 and 24 hours, and analyzed using a UV-VIS spectrophotometer (205 nm). Pharmacokinetic parameters assessed included absorption rate constant (ka), elimination rate constant (ke), half-life (t½), peak time (tmax), maximum concentration (Cpmax), and area under the curve (AUC). Results showed that bay leaf infusion increased Cpmax (2.646 → 3.105 µg/ml), prolonged t½ (3.347 → 16.116 h), and elevated AUC (23.382 → 56.479 µg·h/ml). These findings indicate that bay leaf infusion significantly alters the pharmacokinetic profile of Captopril.